SOCIO-AFFECTIVE STRATEGIES EMPLOYED BY STUDENTS IN SPEAKING CLASS - Robiansyah, Maulid; Rochmahwati, Pryla (Institut Agama Islam Negeri Ponorogo, 2020)
This research is aiming at scrutinizing the socio-affective strategies used by students in speaking class at SMP Ma’arif 1 Ponorogo. This research employed qualitative approach, and the design was case study was conducted on the Eighth Grade B class of SMP Ma’arif 1 Ponorogo, and focused on the description of using socio-affective strategies in teaching speaking at the Eighth Grade B class of SMP Ma’arif 1 Ponorogo. The data in this research is collected through interview, observation, reviewing the documents. The data were analyzed by using data Mattew B Miles and Michael Hubberman’s view of data reduction, data display and drawing conclusion. The result of this research revealed that (1) the implementation of socio-affective starategies is devided into three activities namely; Pre activities, main activities, and the last activities. In pre activities there are two activities, greeting and apperception. In main activities, teacher applied “socio-affective stratgies. The findings that. In the last activities the teacher gave an evaluation and motivation. In evaluation activity a teaching and learning process need to be evaluated. (2) Those the role of the teacher is as follow in supporting the implementation of socio-affective strategies at Eighth Grade B Class of SMP Maarif 1 Ponorogo is very important because as a teacher holds an important position in the learning process. The roles teachers play in English Language Teaching (ELT) field are mostly of an assessor, organizer, facilitator, prompter, motivator, participant, monitor, model, etc.